Mucoadhesive Andrographolide-Loaded Liposomes for Nasal Delivery Modulate Inflammatory Responses in Tumor Necrosis Factor Alpha-Induced Acute Lung Injury in Mice - Mattaka Khongkow; Natchanon Rimsueb; Katawut Namdee; Phichaporn Bunwatcharaphansakun; Rattaporn Saenmuangchin; Narumol Bhummaphan; Charoenchai Puttipanyalears; Papitchaya Watcharanurak; Chaiyos Sirithanakorn; Prapimpun Wongchitrat; Sarawut Lapmanee (ACS Omega, 2025)
studies. The characteristics of AGP-Lip included an average size of 139.7 ± 2.00 nm, a polydispersity index of 0.16 ± 0.02, and a zeta potential of 34.5 ± 0.80 mV, with strong mucoadhesive properties. AGP-Lip exhibited no cytotoxicity in IMR-90 lung fibroblast cells while effectively reducing inflammation by decreasing nitric oxide production in RAW 264.7 murine macrophage cells exposed to lipopolysaccharide. In the animal study, adult male C57BL/6 mice received a single intraperitoneal dose of 100 μg/kg of tumor necrosis factor-α (TNF-α)-induced acute pulmonary systemic inflammation. Mice were randomly assigned to six groups (9 mice per group): control, PBS (negative control), Blank-Lip, AGP-Lip, dexamethasone (POS), and AGP-Lip+POS. All treatments (20 to 25 μL with AGP-Lip, AGP-Lip, and/or POS at 1 mg/kg) were administered via nasal delivery daily for 7 days. The vehicle-treated mice exhibited signs of sickness and systemic inflammation, including reduced body weight gain, hyperlocomotion, decreased exploratory activity, elevated total white blood cell counts, serum IL-6 and TNF-α, and upregulation of targeted mRNA expression of lung inflammatory markers. Histological analysis showed an increase in inflammatory scores, and secretory cells were also observed in the vehicle-treated group. AGP-Lip improved body weight and stress-related behaviors, restored mRNA expression levels of IFN-γ, IL-1α/β, IL-6, IL-10, NF-κBp65, and TNF-α, and alleviated mucus secretion in lung histological analysis. Notably, AGP-Lip effectively mitigated the detrimental effects compared to POS alone, showing significant differences in serum IL-6, lung inflammation-related gene expression (i.e., IFN-γ, IL-1α, NF-κBp50, and VEGF), and PAS staining relative to the combined treatment. These findings suggest that AGP-Lip could serve as a potential alternative treatment for acute respiratory infections, warranting further consideration for long-term administration and clinical trials.
Keywords: Andrographolide Research and Applications; Advanced Drug Delivery Systems; Antimicrobial Peptides and Activities